Study of Antibiotic Use on Pneumonia Patient in Surakarta Referral Hospital - Yeni Farida; Ayu Trisna; Deasy Nur (Universitas Sebelas Maret, 2017)
Pneumonia is lung inflammation, mostly caused by bacteria. Antibiotics are the primary therapy in cases of pneumonia due to bacteria. This study aimed to determine the profiles of pneumonia patients and their use of antibioticsin Surakarta referral hospital.Data were collected retrospectively by using patient's medical recordand prescription on 2014-2015. Subject were obtained by purposive sampling. Patients diagnosed pneumonia with antibiotik therapywere included while patient with comorbide other infection were excluded. The result showed that the most pneumonia patient were aged 0-5 years old (27,71%, female and the average length of stay 11 days) The most single use antibiotik in pediatric patients and adults was ceftriaxone (21.09% and 66.12% respectively) . The combination of antibiotics that were widely used in pediatric patients were ampicillin-gentamicin (39.27%), while in adult patients were ceftriaxone and azithromycin (26.97%).